Margin Pemasaran Produk Captikus Di Desa Wuwuk Kecamatan TareranKabupaten Minahasa Selatan - Lintong, Frityliya Syutrisje; Pakasi, Caroline Betsi Diana; Timban, Jean Fanny Junita (AGRI-SOSIOEKONOMI, 2024)
The purpose of this study is to analyze and determine the amount of marketing margin for each marketing channel of captikus in Wuwuk Village, Tareran District. The research was conducted over three months from June to August 2023, in Wuwuk Village, Tareran District. The study used two types of data: primary data obtained through direct interviews with respondents using a structured questionnaire, and secondary data obtained from the internet, including journals, theses, and other relevant information related to the research. The sampling technique employed was purposive sampling, a method of selecting samples based on specific considerations. A total of 18 captikus farmers and 1 collector trader were sampled. The data analysis included marketing margin, marketing costs, marketing profit, and farmer share. The results show that in captikus marketing in Wuwuk Village, Tareran District, there are two types of marketing channels: Channel I, which involves sales from farmers to consumers with a marketing margin cost of Rp0, and Channel II, which involves sales from farmers to collectors and then to consumers, with a marketing margin cost of IDR3,549.